The Implementation of the Demonstration Method Through Flashcard Media to Enhance English Vocabulary Comprehension in Elementary School Students (MI/SD) - Rosyidi, Zudan; Lailiyah, Nishfatul (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
This research aims to describe the application of the demonstration method using flashcard media to enhance English vocabulary comprehension among MI/SD (elementary school) students. The research methodology employed a qualitative approach with a phenomenological research design. Data were gathered through observations, interviews, and documentation, focusing on describing the implementation of the demonstration method via flashcard media to improve English vocabulary comprehension among students at MI Nurul Huda. The research participants included class teachers and several students at MI Nurul Huda. Following data collection, an analysis was conducted on the gathered data. The research findings indicate that the implementation of the demonstration method using flashcard media at MI Nurul Huda has been successful. The utilization of this demonstration method through flashcard media has significantly assisted students in mastering English vocabulary. Additionally, this method has also supported teachers in enhancing student learning outcomes. Furthermore, the demonstration method using flashcard media has motivated and boosted students' enthusiasm for learning during the educational process. In the application of the demonstration method using flashcard media for English language learning at MI Nurul Huda, several challenges were identified. These challenges include time limitations affecting the delivery of material to students and a lack of reading interest among students. Another significant challenge is the students' awareness in applying the learned vocabulary. Despite the challenges, the implementation of the demonstration method using flashcard media has provided a positive impact on the English vocabulary comprehension of students at MI Nurul Huda.